Self-Confidence and Hedonism : Identifying The Social Behavior of Junior High School Student - Rosada Rosada; Yuda Syahputra; Haryanto Haryanto (Jurnal Keilmuan Pendidikan, 2025)
The purpose of this study is to determine the self-confidence profile of students at SMPN 67 Jakarta, to examine the hedonism tendencies among these students, and to investigate whether there is an influence of self-confidence on hedonism. This research employs a descriptive quantitative approach. The population consisted of 180 students, and based on the Slovin formula for random sampling, a total of 124 students were selected as the sample. Data were processed using IBM SPSS version 20 with a simple linear regression analysis technique. The results of the data analysis show a t-value of -5.738 with a significance value of 0.000 < 0.005, indicating that the independent variable (self-confidence) has a significant influence on the dependent variable (hedonism). Thus, the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It can therefore be concluded that the higher an individual's self-confidence, the lower their tendency toward hedonism, and vice versa. The analysis also shows an R square value of 0.213, meaning that self-confidence contributes 21.3% to the variation in hedonism, while the remaining 78.7% is influenced by other factors beyond self-confidence.